Explaining political culture across different socioeconomic and institutional settings using evidence from Latin America and Europe - Belchior, Ana Maria; Ribeiro, E; Queiroga, V.; Borba, J.; Viegas, J.M. Leite (Conferência FCT-CAPES “Instituições, atitudes e comportamentos políticos em tempos de mudança”, 2017)
Most studies on political culture have been descriptive or explored political culture as an independent variable to explain a country's socioeconomic characteristics and/or its political institutions' performance. Much less research focused on what explains a country's political culture. Furthermore, education has been acknowledged as a core variable in explaining individuals' political attitudes and values, but has seldom been used to explain national political culture. Our research focuses on these less explored perspectives, using national political culture as a dependent variable. To what extent different socioeconomic and institutional settings influence a country's political culture? And what is the importance of individuals' level of education in such relationships? To answer these questions we rely on a broad range of political systems in Europe and Latin America (54), between 2002 and 2014, using data of the European Social Survey and LatinoBarómetro. Findings significantly support our claim that socioeconomic contexts and institutional settings matter in explaining a country’s political culture, and that these contextual differences modulate the effect of education.